PENGARUH PELATIHAN, IKLIM ORGANISASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH PROVINSI SUMATERA UTARA - Monica Dwi Suci; Julianto Hutasuhut; Abd Rasyid Syamsuri; Adrial Falahi (Bisnis-Net, 2023)
This study aims to analyze the effect of training, organizational climate and competence on the performance of employees of the Regional Tax and Retribution Management Agency of North Sumatra Province. The type of research used is quantitative. the study population amounted to 265 civil servants (ASN). The sampling technique used was subjectively purposive sampling. Thus, the number of samples in this study were 84 Civil Servants (PNS). Data collection techniques used were observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the Statistical Product Software Solution (SPSS) program. The results of the t test show that training has a positive and significant effect on employee performance, organizational climate has a positive and significant effect on employee performance and competence has a positive and significant effect on employee performance at the Regional Tax and Retribution Management Agency of North Sumatra Province. Simultaneously training, organizational climate and competence have a positive and significant effect on the performance of employees of the Regional Tax and Retribution Management Agency of North Sumatra Province. The adjusted coefficient of determination (R Square) is 0.703, this means that 70.3% of the dependent variable can be explained by the independent variable while the rest (100% - 70.3% = 29.7%) is explained by other variables outside the variables studied.Keywords: Training, Organizational Climate, Competence, Employee Performance